Leave events among Aboriginal and Torres Strait Islander people: a systematic review - J Coombes; K Hunter; K Bennett-Brook; B Porykali; C Ryder; M Banks; N Egana; T Mackean; S Sazali; E Bourke; C Kairuz (BMC, 2022)
Abstract Background Leave events are a public health concern resulting in poorer health outcomes. In Australia, leave events disproportionally impact Aboriginal and Torres Strait Islander people. A systematic review was conducted to explore the causes of leave events among Aboriginal and Torres Strait Islander people and strategies to reduce them. Methods A systematic review was conducted using Medline, Web of Science, Embase and Informit, a database with a strong focus on relevant Australian content. Additionally, we examined the references of the records included, and performed a manual search using Google, Google scholar and the Australia's National Institute for Aboriginal and Torres Strait Islander Health Research. Two independent reviewers screened the records. One author extracted the data and a second author reviewed it. To appraise the quality of the studies the Mixed Methods Appraisal Tool was used as well as the Aboriginal and Torres Strait Islander Quality Appraisal Tool. A narrative synthesis was used to report quantitative findings and an inductive thematic analysis for qualitative studies and reports. Results We located 421 records. Ten records met eligibility criteria and were included in the systematic review. From those, four were quantitative studies, three were qualitative studies and three reports. Five records studied data from the Northern Territory, two from Western Australia, two from New South Whales and one from Queensland. The quantitative studies focused on the characteristics of the patients and found associations between leave events and male gender, age younger than 45 years and town camp residency. Qualitative findings yielded more in depth causes of leave events evidencing that they are associated with health care quality gaps. There were multiple strategies suggested to reduce leave events through adapting health care service delivery. Aboriginal and Torres Strait Islander representation is needed in a variety of roles within health care provision and during decision-making. Conclusion This systematic review found that multiple gaps within Australian health care delivery are associated with leave events among Aboriginal and Torres Strait Islander people. The findings suggest that reducing leave events requires better representation of Aboriginal and Torres Strait Islander people within the health workforce. In addition, partnership with Aboriginal and Torres Strait Islander people is needed during the decision-making process in providing health services that meet Aboriginal and Torres Strait Islander cultural needs.